Doing Ethnography of Policies against Sexual Violence: Perspectives for a Case Study in the Universities of Montreal - Farneti, Alice (Cahiers d'histoire)

(untitled) (Cahiers d'histoire, 2023)
This article discusses some of the problematics that inform the methodology of my ongoing doctoral research on policies against sexual violence in Montreal universities. First, I will argue that feminist activists in Quebec have been able to expose the institutional dimension of sexual violence in university. Then, I will then compare Dorothy Smith’s institutional ethnography approach with Sara Ahmed’s phenomenological approach to institutions to elaborate on the concept of lived experience as a starting point for the investigation of institutional regimes. In conclusion, I will engage with Nancy Naples’ outsider/insider debate to reflect on the multiplicity of divergent and contradicting perspectives in the field.